2022
DOI: 10.1021/acs.joc.2c01141
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonium and Selenonium Salts as Noncovalent Organocatalysts for the Multicomponent Groebke–Blackburn–Bienaymé Reaction

Abstract: Sulfonium and selenonium salts, represented by S-aryl dibenzothiophenium and Se-aryl dibenzoselenophenium triflates, were found to exhibit remarkable catalytic activity in the model Groebke–Blackburn–Bienaymé reaction. Kinetic analysis and density functional theory (DFT) calculations indicated that their catalytic effect is induced by the ligation of the reaction substrates to the σ-holes on the S or Se atom of the cations. The experimental data indicated that although 10-fold excess of the chloride totally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 84 publications
(135 reference statements)
3
25
0
Order By: Relevance
“…In the case of the nucleophilic addition of ammonia to the carbonyl group (TS2), the total electronic energy of activation is reduced for 1-9 from −11 kJ mol Although the experimental data on the relative catalytic activity between the ChB-and XB-donating organocatalysts are scarce, the computational results obtained by Method 2 seem to be more coherent with our recent works on the experimental determination of the catalytic activity of onium salts. 68,71 Thus, it has been found for the Groebke-Blackburn-Bienaymé multicomponent reaction including the electrophilic activation of the carbonyl group that the iodonium salt 9 OTf exhibits significantly higher catalytic activity than the selenonium salt 5 OTf , which, in turn, provides a slightly higher catalytic effect than the sulfonium salt 4 OTf . 55,68,71 In addition, Yoshida and his co-workers have shown that iodonium salts exhibit a significantly higher catalytic effect than bromonium and chloronium salts 55 (see Fig.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of the nucleophilic addition of ammonia to the carbonyl group (TS2), the total electronic energy of activation is reduced for 1-9 from −11 kJ mol Although the experimental data on the relative catalytic activity between the ChB-and XB-donating organocatalysts are scarce, the computational results obtained by Method 2 seem to be more coherent with our recent works on the experimental determination of the catalytic activity of onium salts. 68,71 Thus, it has been found for the Groebke-Blackburn-Bienaymé multicomponent reaction including the electrophilic activation of the carbonyl group that the iodonium salt 9 OTf exhibits significantly higher catalytic activity than the selenonium salt 5 OTf , which, in turn, provides a slightly higher catalytic effect than the sulfonium salt 4 OTf . 55,68,71 In addition, Yoshida and his co-workers have shown that iodonium salts exhibit a significantly higher catalytic effect than bromonium and chloronium salts 55 (see Fig.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
“…68,71 Thus, it has been found for the Groebke-Blackburn-Bienaymé multicomponent reaction including the electrophilic activation of the carbonyl group that the iodonium salt 9 OTf exhibits significantly higher catalytic activity than the selenonium salt 5 OTf , which, in turn, provides a slightly higher catalytic effect than the sulfonium salt 4 OTf . 55,68,71 In addition, Yoshida and his co-workers have shown that iodonium salts exhibit a significantly higher catalytic effect than bromonium and chloronium salts 55 (see Fig. 4, energy diagram for Method 2).…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
See 3 more Smart Citations